A review on dynamics and policies of knowledge transfer between university and industry. (1st March 2022) - Anatan, Lina
This article discusses a literature review regarding the dynamics and policies adopted by the government to manage knowledge transfer. This paper also discusses knowledge transfer activities in Japan, which is focused on the model of knowledge transfer and policies implemented in Japan and the importance of regulative pressure to optimise the transfer of knowledge. Literature on knowledge transfer between university and industry, specifically in Indonesia, is still limited and lead to the gap on related studies. This literature review was conducted to fill the gap that focused on dynamics and policies of knowledge transfer between university and industry. Through the discussion, it is expected to give insights and lesson learned for organisations in Indonesia to manage knowledge transfer activities between universities and industries.